Supramolecular Assemblies for Transporting Proteins Across an Immiscible Solvent Interface - Gao, Jingjing (J Am Chem Soc, 2018)
Polymeric supramolecular assemblies that can effectively transport proteins across an incompatible solvent interface are described. We show that electrostatics and ligand-protein interactions can be used to selectively transport proteins from an aqueous phase to organic phase. These transported proteins have been shown to maintain their secondary structure and function. This approach opens up new possibilities for application of supramolecular assemblies in sensing, diagnostics and catalysis.